2021
DOI: 10.1080/19336950.2021.1910461
|View full text |Cite
|
Sign up to set email alerts
|

Potassium channels as molecular targets of endocannabinoids

Abstract: Endocannabinoids are a group of endogenous mediators derived from membrane lipids, which are implicated in a wide variety of physiological functions such as blood pressure regulation, immunity, pain, memory, reward, perception, reproduction, and sleep. N-Arachidonoylethanolamine (anandamide; AEA) and 2-arachidonoylglycerol (2-AG) represent two major endocannabinoids in the human body and they exert many of their cellular and organ system effects by activating the G i/o protein-coupled, cannabinoid type 1 (CB1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 110 publications
(250 reference statements)
1
6
0
Order By: Relevance
“…Furthermore, K ATP expressed in Xenopus oocytes were inhibited by AEA (CBR independent) with an IC 50 of 8.1 µM (Oz et al, 2007), but activated in rat ventricular myoctyes in a CB2 dependent manner (Li et al, 2012). Notably, the EC 50 ’s of the endocannabinoids studied here on Kir2.1 and Kir4.1 are in a similar range of IC 50 /EC 50 ’s identified for a variety of other channels (Lin, 2021), and thus physiologically relevant.…”
Section: Discussionsupporting
confidence: 60%
“…Furthermore, K ATP expressed in Xenopus oocytes were inhibited by AEA (CBR independent) with an IC 50 of 8.1 µM (Oz et al, 2007), but activated in rat ventricular myoctyes in a CB2 dependent manner (Li et al, 2012). Notably, the EC 50 ’s of the endocannabinoids studied here on Kir2.1 and Kir4.1 are in a similar range of IC 50 /EC 50 ’s identified for a variety of other channels (Lin, 2021), and thus physiologically relevant.…”
Section: Discussionsupporting
confidence: 60%
“…Endocannabinoids activating TRPV1 have been included in the endovanilloid system [337][338][339]. Recent studies suggest that potassium channels are also the targets of endocannabinoids [340].…”
Section: Endogenous Receptors For Aea and 2-agmentioning
confidence: 99%
“…A potential mechanism might be the inhibition of Na + channels by AM251, which reduces neuronal excitability through blockade of voltage-sensitive Na + channels in the brain [ 35 ]. Another non mutually exclusive possibility is that effects could be due to (endo)-cannabinoid-mediated modulation of BK channels as it has been reported that (endo)-cannabinoids directly interact with and can modify BK channel activity [ 36 ]. As a result, AM251’s effects on modulating excitability changes seen in the 3-AP Purkinje cells could be via modulation of BK function.…”
Section: Discussionmentioning
confidence: 99%